A Chance Constrained Approach for Uplink Wireless Ofdma Networks - Soto-Gomez, J; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2014)
In this paper, we compare individual and joint probabilistic constraints for a resource allocation problem in an uplink (UL) wireless OFDMA network. For this purpose, we formulate the problem as a stochastic linear programming (SLP) problem. Then, we transform this model into equivalent deterministic Second-Order Cone Programming (SOCP) problems. All models are intended to maximize the bit rates throughput of the network subject to subcarrier and power user constraints. Our preliminary numerical results show that the joint chance constraint formulation is slightly conservative than the individual probabilistic one. Finally, we show that our approximation of the deterministic joint probabilistic model is very tight. © 2014 IEEE.